Soroprevalência da infecção por Toxoplasma gondii e Neospora caninum em suínos de propriedades de subsistência no estado de Mato Grosso - Minetto, Make Kawatake (2018)
To evaluate the prevalence of anti-Toxoplasma gondii and anti-Neospora caninum antibodies and identify the risk factors associated with these infections, serum samples were collected from 1,070 pigs from 320 backyard pig farming establishments in the state of Mato Grosso, Brazil. Each farmer was asked to fill out a questionnaire for subsequent epidemiological data analysis. Anti-T. gondii and anti-N. caninum antibodies were detected using the indirect immunofluorescent assay (IFA) with cut-off dilutions of 1:64 and 1:50, respectively. The overall prevalence of anti-T. gondii and anti-N. caninum antibodies was 32.48% and 13.49%, respectively, while the prevalence per herd was 55.63% for T. gondii and 27.81% for N. caninum. Pigs fed with leftovers were 1,0989 times more likely to test positive for anti-T. gondii antibodies, while age of the pigs and feeding with leftovers were the significant variables associated with positive results for anti-N. caninum antibodies. Furthermore, farms that provided leftover food s were 38.13% less likely to have pigs testing positive for N. caninum. Further studies are necessary to evaluate the impact of T. gondii infection in backyard pig farming production, its importance as a source of toxoplasmosis infection in humans in the Mato Grosso state, and the role of domestic pigs in the epidemiology of neosporosis.